2016
DOI: 10.1016/j.biomaterials.2016.01.062
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal control of cardiac anisotropy using dynamic nanotopographic cues

Abstract: Coordinated extracellular matrix spatiotemporal reorganization helps regulate cellular differentiation, maturation, and function in vivo, and is therefore vital for the correct formation, maintenance, and healing of complex anatomic structures. In order to evaluate the potential for cultured cells to respond to dynamic changes in their in vitro microenvironment, as they do in vivo, the collective behavior of primary cardiac muscle cells cultured on nanofabricated substrates with controllable anisotropic topogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 51 publications
0
42
0
Order By: Relevance
“…Mengsteab et al . recently reported that these PCL-SMP-based nanotopographic cues are capable of serving as instructive signals that dynamically regulate the structural and contractile properties of neonatal rat ventricular myocytes (NRVMs) into a well-defined anisotropic monolayer [162]. Indeed, the orthogonal transition of anisotropic nanogrooves could be used to directly manipulate the contractile direction of cardiac cell sheets (Figure 9B).…”
Section: Dynamic Mechano-structural Cuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Mengsteab et al . recently reported that these PCL-SMP-based nanotopographic cues are capable of serving as instructive signals that dynamically regulate the structural and contractile properties of neonatal rat ventricular myocytes (NRVMs) into a well-defined anisotropic monolayer [162]. Indeed, the orthogonal transition of anisotropic nanogrooves could be used to directly manipulate the contractile direction of cardiac cell sheets (Figure 9B).…”
Section: Dynamic Mechano-structural Cuesmentioning
confidence: 99%
“…The kurtosis of contraction direction after shape transition decreases, and a 49 degree shift of the contraction angle peak is observed (kurtosis = 2.45, 0.31 before and after, respectively. *p < 0.001, n = 3, paired t-test) [162]. (C) Shape memory assisted dynamic microwrinkle display system.…”
Section: Figurementioning
confidence: 99%
“…Parallel nano-grooves and nano-ridges help maintain the cell polarity and alignment important for organ development by providing contact guidance which influences the organization of microtubules, focal contacts, and actin filaments in parallel with the underlying topography (Kim et al, 2012b). Investigations with cardiomyocytes on dynamically shifting topographies demonstrate the capacity for such cells to reorient themselves in real-time, according to changes in substrate cues, mirroring cells’ capacity to remodel in vivo in response to damage or alterations in mechanical strain (Mengsteab et al, 2016). Similarly, cells cultured on ECM fibers and microgrooves aligned with electrical stimulation patterns have also shown increased elongation, alignment, and electrical functionality (Kim et al, 2010, Kim et al, 2013b) (Figure 3A–C).…”
Section: Biomimetic Strategies For Human Cardiac Tissue Engineeringmentioning
confidence: 99%
“…In addition, although great care is usually given to the temporal regulation of chemical factors used in several protocols (during somatic cell reprogramming [27] for instance), there is no reason to assume that mechanical regulation is not just as important. In fact, a recent study utilizing tunable polymeric materials to study the effects of parameters such as anisotropic topgraphic cues [28] or stress relaxation [29] reveal highly dynamic cellular responses. Therefore, there is a need for in-vitro cell culture platforms with externally tunable mechanical properties in order to study the temporal effect of these parameters [30] .…”
Section: Introductionmentioning
confidence: 99%